MODEL PEMBELAJARAN SEJARAH TIPE JIGSAW BERBASIS ARSIP SEJARAH LOKAL UNTUK MENGUATKAN BERPIKIR HISTORIS PESERTA DIDIK - Eva Setianingsih; Umi Hartati (Swarnadwipa, 2020)
The research objectives are (1) to describe the history learning model that has been used in class XI of Muhammadiyah 2 High School in SMA (2) to describe the level of students' historical thinking ability on the local history of the material impact of colonialism and imperialism policies on the development of Metro City class XI of Muhammadiyah 2 Senior High School Metro (3) To obtain a Jigsaw type historical learning model design based on local history archives in the history subjects of class XI Muhammadiyah 2 Metro High School (4) To describe the opinions of experts about the feasibility of developing a historical learning model based on local history archive Jigsaw to strengthen thinking skills historicallyclass XI of Muhammadiyah 2 Metro High School. Research uses research and development (R&D) methods. After producing a draft of the product validation is carried out by a team of experts namely material experts and design and model experts, distributing questionnaires to students to see the level of students' historical thinking. The results of the study are (1) learning models used in Muhammadiyah 2 Metro High School such as cooperative learning (type of student teams achievement division, jigsaw), problem based learning models, direct learning models, Discovery Learning (DL), Collaborative Learning (CBL); (2) the design of Jigsaw type history learning model development based on local history archives was designed in accordance with KI and KD curriculum 2013; (3) the results of validation by stage 1 material experts were 75% (Eligible) stage 2 by 92% (Very Eligible), between stage 1 and stage 2 increased by 17%. The results of validation by design experts and stage 1 models were 78% (Eligible), stage 2 was 93% (Very Eligible), stage 1 and stage 2 increased by 15%. Based on the results of the validation, it shows that the design book of Jigsaw history learning model based on local history archives is worth testing.